Seroprevalence of measles, mumps, rubella, varicella-zoster and hepatitis A-C in Emirati medical students - Sheek-Hussein Mohamud; Hashmey Rayhan; Alsuwaidi Ahmed R; Al Maskari Fatima; Amiri Leena; Souid Abdul-Kader (BMC, 2012)
Abstract Background The aims of this study were to assess the seroprevalence of vaccine-preventable infections in Emirati medical students, and to provide scientific evidence for implementation of a cost-effective immunization guideline and policy for medical school admission. Methods This prospective cohort study involved 261 (61% female) Emirati medical students (preclinical and clinical) attending the College of Medicine and Health Sciences at UAE University. Data on vaccination and history of infectious diseases were collected from participants. Blood samples were collected between July 1, 2011 and May 30, 2012 for serological testing and QuantiFERON®-TB assay. Results All students tested negative for infection with hepatitis C virus and human immunodeficiency virus. The prevalence of seropositivity to rubella virus was 97%, varicella-zoster virus 88%, mumps virus 84%, measles virus 54%, hepatitis B virus (HBV) 48%, and hepatitis A virus 21%. The QuantiFERON®-TB test was positive in 8% and indeterminate in 2%. Forty percent of students received HBV vaccine at birth; their HBV titers (mean ± SD) were 17.2 ± 62.9 mIU/mL (median = 1.64). The remaining 60% received it at school and their titers were 293.4 ± 371.0 mIU/mL (median = 107.7, p = 0.000). Conclusion About 50% of students were susceptible to HBV and measles virus; therefore, pre-matriculation screening for antibodies against these viruses is highly recommended. Moreover, tuberculosis screening is necessary because of the high influx of expatriates from endemic areas. Students with inadequate protection should be reimmunized prior to contact with patients.